A proposal for the establishment of an acceptable noise environment in architectural studios - Gurturk, Semran Ozdem (Gazi Univ, 2026)
In architectural education, architectural studios are the environments where designers spend most of their time, where mutual communication and teachings about design methods are discussed the most. Education in architectural studios is based on a system of learning by doing and a constant flow of verbal and visual information. In this system, user satisfaction depends on the presence of building physics comfort conditions in design studios. In this regard, ensuring speech intelligibility and acoustic arrangements become important in design studios that are used constantly. In this study, an architectural studio with mutual conversation and constant information flow, noise factor and high number of users was discussed. The architectural studio was modeled and the current noise level was determined through the SoundPlan 8.2 simulation program. An acoustically comfortable studio model with appropriate surface absorption has been tried to be created through the program that allows the transfer of different surface absorptions. Three architectural studio models were designed according to the number of users and the size of the volume. The total absorption values required to provide optimum acoustic comfort conditions in these volumes were determined with the help of graphs created as a result of the analysis. In relation to the arrangements made and noise control, it will be possible to determine whether the acoustic comfort limit value is met by evaluating the graphics and noise maps obtained with simulation programs.
Keywords: Architectural studio; acoustic comfort; acoustic design parameters